CUMULATE XENOLITHS IN OLIGOCENE ALKALINE BASALTIC AND LAMPROPHYRIC DIKES FROM THE EASTERN RHODOPES, BULGARIA: EVIDENCE FOR THE EXISTENCE OF LAYERED PLUTONS UNDER THE METAMORPHIC CORE COMPLEXES - Marchev P.; Arai S.; Vaselli O. (My University, 2006)
Ultramafic and mafic xenoliths entrained in late Oligocene dikes of intraplate origin provide information about the composition of the lower crust and the processes operating beneath the eastern Rhodope metamorphic core complexes Biala Reka and Kesebir, in southeastern Bulgaria. The cumulates comprise a series of high- to medium-pressure rocks represented by olivine websterites, orthopyroxenites, clinopyroxenites, websterites, and gabbros. Thermobarometric studies and comparison with experimental works suggest that the cumulate sequence formed from hydrous (>3 wt%) mafic magma at pressures of 14-9 kilobars (45-30 km) and temperatures of 1200-850 °C. It is inferred that underplating of such hot, wet mafic intrusions modified the thermal and mechanical properties of the lower and middle crust, as is reflected in thermal metamorphism, associated extension, and hydrothermal activity producing low-sulfidation Au deposits. Findings of similar xenoliths in the alkaline basalts from other extended regions such as the eastern Mediterranean and the Basin and Range Province indicate that underplating of mafic magma plays an important role in core complex formation. © 2006 Geological Society of America.
Keywords: EASTERN RHODOPES; METAMORPHIC CORE COMPLEX; ULTRAMAFIC AND MAFIC XENOLITHS; UNDERPLATING; Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен